Variations of Bacterial Community Diversity Within the Rhizosphere of Three Phylogenetically Related Perennial Shrub Plant Species Across Environmental Gradients - Na, Xiaofan; Xu, Tingting; Li, Ming; Zhou, Zhaona; Ma, Shaolan; Wang, Jing; He, Jun; Jiao, Bingzhong; Ma, Fei (Frontiers in Microbiology, 2018)
Rhizosphere microbial communities are of great importance to mediate global biogeochemical cycles, plant growth, and fitness. Yet, the processes that drive their assembly remain unclear. The perennial shrubs Caragana spp., which is well known for their role in soil and water conservation, provides an ideal system to study the biogeography of rhizosphere microorganism communities within natural ecosystems. In order to detect how bacterial rhizosphere communities vary in terms of community diversity and composition, the rhizosphere bacterial community of three Caragana species, C. microphylla Lam., C. liouana Zhao, and C. korshinskii Kom., which distributed in arid and semi-arid region of northern China were investigated. Across species, Proteobacteria (61.1%), Actinobacteria (16.0%), Firmicutes (8.6%), Bacteroidetes (3.0%), Acidobacteria (3.5%), Gemmatimonadetes (1.4%), and Cyanobacteria (1.0%) were the most dominant phyla in the rhizosphere of the three Caragana species. The relative abundance of Cyanobacteria was significantly higher in rhizosphere of C. korshinskii Kom. compared with C. microphylla Lam. and C. liouana Zhao, while the opposite was found for Gemmatimonadetes in rhizosphere of C. microphylla Lam. relative to C. liouana Zhao. Stepwise multiple linear regression analysis showed that both diversity and richness of the bacterial rhizosphere communities significantly and positively correlated with soil pH (p < 0.01). Distance-based redundancy analysis indicated that soil properties and non-soil parameters detected there accounted for 47.5% of bacterial phylogenetic structure variation (p < 0.01) all together. Meanwhile, soil total phosphorus accounted for the greatest proportion of community structure variance (9.7%, p < 0.01), followed by electrical conduction (6.5%), altitude (5.8%), soil pH (5.4%), mean annual precipitation (3.6%) and total nitrogen (3.6%, p < 0.05 in all cases). Furthermore, partial Mantel test suggested that bacterial rhizosphere community structure significantly correlated with geographical distance, indicating that the less geographical distant sample sites tend to harbor more similar bacterial rhizosphere community. Our results shed new light on the mechanisms of coevolution and interaction between long-lived plants and their rhizosphere bacterial communities across environmental gradients.